Adubação nitrogenada na produção e na qualidade de frutos de maracujazeiro amarelo - Tosta, Mauro da Silva (2009)
The culture of the passion fruit plant-yellow it is explored commercially of north to south of Brazil, involving tropical and subtropical areas. Your cultivation is in expansion phase in reason of the great commercialization perspectives. In this context the objective of the work was to evaluate the effect of the manuring nitrogenada in the production of the yellow passion fruit plant irrigated in the conditions of Cassilandia (MS). The experimental design used was of randomized complete blocks whit 5 doses of nitrogen (0, 80, 160, 240 and 320 kg ha-1), with 4 repetitions, spaced in 3m between lines and 4m among plants; each experimental unit was constituted by 6 plants and 4 plants in the useful area. The conduction in the culture was accomplished in a wire thread to 1,8m of height of the soil. The application of the treatments was parceled out in 6 times (from 11/2006 to 05/2007), beginning 5 months after transplant of the seedlings. The crop was it accomplishes from 29/11/2006 to 17/08/2007. The increase of the manuring with nitrogen promoted an answer of behavior quadratic polinomial for the total of fruits you didn't trade; total of fruits; production commercial, no-commercial and total; commercial and no-commercial productivity; thickness of the peel; and SST. The increase of the doses of N promoted a decreasing answer for medium weight of marketable fruits; pulp revenue; number of seeds; and pH of the soil. Not being verified effect of the treatments for total of marketable fruits, weigh medium, diameter and fruit length; and pH of the pulp. The manuring with nitrogen influences in the production and the quality of the passion fruit plant-yellow, in the conditions of Cassilandia (State of Mato Grosso do Sul - Brazil), it can be applied from 116 to 173 kg ha-1 of nitrogen in covering.